Correlative Analysis Between Adverse Events of Preoperative Chemotherapy and Postoperative Complications of Gastric Cancer - Wu, Zhouqiao; Wang, Yiding; Hou, Shiyang; Wang, Qi; Li, Bailong; Ying, Xiangji; Li, Shuangxi; Li, Ziyu; Ji, Jiafu (Frontiers in Surgery, 2021)
Background and Objectives: This study aims to explore the safety of preoperative chemotherapy and clarify whether preoperative chemotherapy with oxaliplatin + S-1 (SOX) regimen and its adverse events are associated with higher risks of postoperative complications. Methods: We included consecutive patients with gastric cancer who underwent gastrectomy in our department between July 1 2018, and January 31 2020. Patients with preoperative SOX regimen chemotherapy were included in the analysis. Results: In the 343 included patients, 77 cases underwent preoperative chemotherapy. In total, surgical complications were found in 117 patients (34.1%), and there was no significant difference between the patients with and without preoperative chemotherapy before and after propensity score matching (p > 0.05, respectively). Multivariate analysis showed that preoperative comorbidities (p = 0.026) and the preoperative cT4b (p = 0.028) were independent risk factors in postoperative complications. In patients with preoperative chemotherapy, neither the occurrence of adverse events nor their severity was associated with postoperative complications (p > 0.05). However, the patients who received five to six cycles were more prone to postoperative complications than those who received three to four cycles (62.5 vs. 27.9%, OR = 4.306, 95% Cl = 1.282–14.464, p = 0.018). Conclusions: Occurrence of postoperative complications was not influenced by preoperative SOX chemotherapy. However, increased cycles of chemotherapy may lead to higher incidence of postoperative complications.